THE ROLE OF WORK MOTIVATIOM IN MODERATING THE EFFECT OF COMPENSATION ON WORK PRODUCTIVITY OF AMIL ZAKAT (Study at the Amil Zakat Institute in Bandung City) - Hilda Monoarfa; Salma Khairun Nisa; Fitranty Adirestuty (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2021)
The potential for zakat in Indonesia in 2019 is valued at IDR 233.8 trillion, but the realization is still far from expected because BAZNAS is only able to manage 3.5% of its potential. One of these factors is that LAZ's human resources are still less competent in their fields. Work productivity is still low, so that the distribution of zakat is still consumptive and creates a lack of public trust in LAZ. This study aims to test the organizational behavior theory by analyzing the effect of compensation on amil's work productivity and how work motivation in moderating this effect. With a total sample of 87 respondents, taken using a sampling technique referring to cluster random sampling or random sampling techniques cluster (group), namely the population is divided into smaller sub-units then, obtained from the partial selection of units or better known as primary units, until finally selecting units within the selected primary unit. This research uses the method of causality with a quantitative approach. The data collection technique uses primary data through a questionnaire. The data analysis technique uses Moderated Regression Analysis. The results showed that the level of compensation was in the medium category, the level of work motivation and work productivity was mostly in the high category, and that compensation had a positive effect on amil's work productivity and work motivation did not moderate the relationship between compensation and amil's work productivity, but work motivation had a positive effect on amil work productivity.